The effect of the Covid‐19 pandemic on illness perceptions of psoriasis and the role of depression: Findings from a cross‐sectional study. Issue 3 (3rd July 2022) - Lada, Georgia; Chinoy, Hector; Talbot, Peter S.; Warren, Richard B.; Kleyn, C. Elise
Abstract: Background: Illness perceptions in psoriasis have an impact on adherence and disability. Changes in dermatological healthcare provision during the Covid‐19 pandemic and distress may have affected illness perceptions in psoriasis patients. Objectives: To test whether illness perceptions about psoriasis changed during the first year of the Covid‐19 pandemic compared to pre‐pandemic in a tertiary population with psoriasis and whether pandemic effects differed depending on depressive burden, given this population's high depression prevalence. Methods: In a cross‐sectional survey of n  = 188 tertiary patients with dermatologist‐confirmed psoriasis recruited before and during the pandemic, eight illness perceptions domains were assessed using the Brief‐Illness Perceptions Questionnaire (BIPQ). Presence of depression was assessed with the Hospital Anxiety and Depression Scale (HADS). Results: Beliefs about treatment control and patients' understanding of psoriasis were significantly worse in patients responding during the pandemic compared to before Covid‐19. These differences were greater when depression was absent (treatment control: adjusted p  < 0.001; coherence: adjusted p  = 0.01). However, participants during the pandemic felt less emotionally affected (adjusted p  = 0.02) and concerned (adjusted p  = 0.007) about psoriasis, independently of depression. Conclusions: We found diverse pandemic effects on illness perception domains in psoriasis. Uncertainty and reduced healthcare access may drive poorer treatment and coherence beliefs during Covid‐19. These beliefs can hinder patients' health‐promoting behaviours and may explain the high pandemic non‐adherence reported previously in psoriasis. Appropriate interventions are needed to establish positive long‐term cognitions and improve psoriasis management, for example, using the PsoWell patient materials. Dermatology services should invest in engaging and educating patients regardless of concurrent psychological distress. Abstract :